2022
DOI: 10.1007/s12325-022-02083-8
|View full text |Cite|
|
Sign up to set email alerts
|

Treatment Regimens for Transplant-Ineligible Patients With Newly Diagnosed Multiple Myeloma: A Systematic Literature Review and Network Meta-analysis

Abstract: Introduction: Many treatment regimens have been evaluated in transplant-ineligible (TIE) patients with newly diagnosed multiple myeloma (NDMM). The objective of this study was to compare the efficacy of relevant therapies for the treatment of TIE patients with NDMM. Methods: Progression-free survival (PFS) and overall survival (OS) from large randomised controlled trials (RCTs) evaluating different treatment options for TIE patients with NDMM were compared in a network meta-analysis (NMA). The NMA includes rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…Similar questions exist also for the non-transplant-eligible patients, where the positive impact of continuous treatment on OS is not well demonstrated ( 71 , 73 , 74 ). Clinical trials where MRD-negative patients are randomized to therapy suspension or continuation until disease progression or intolerance will prove informative.…”
Section: Minimal Residual Disease In Therapeutic Decision: Ready For ...mentioning
confidence: 83%
“…Similar questions exist also for the non-transplant-eligible patients, where the positive impact of continuous treatment on OS is not well demonstrated ( 71 , 73 , 74 ). Clinical trials where MRD-negative patients are randomized to therapy suspension or continuation until disease progression or intolerance will prove informative.…”
Section: Minimal Residual Disease In Therapeutic Decision: Ready For ...mentioning
confidence: 83%
“…TTNT curves for VRd were derived by applying PFS hazard ratios from a published network meta-analysis. 18 A TTNT HR for VRd was not available; however, in similar studies, the HRs for TTNT and PFS are usually very similar (eg, in MAIA, PFS HR was 0.53 [95% CI, 0.43-0.66] and TTNT HR was 0.47 [95% CI, 0.37-0.59] 12 ). Therefore, PFS HR was used as a proxy in the current model.…”
Section: Methodsmentioning
confidence: 99%
“…To inform 1L, 1-month transition probabilities were derived from time to next treatment (TTNT; defined as time to next treatment line or death), PFS, and OS data from the MAIA trial 12 , 17 and SWOG S0777 (based on a published network meta-analysis 18 ). Real-world data from the Flatiron Health database were used to inform 2L.…”
Section: Methodsmentioning
confidence: 99%
“…A network meta-analysis by Facon et al (2022) showed that daratumumab-based regimens, including D-Rd, D-VMP, and VRd, had the highest probabilities of being more effective than Rd continuous in terms of PFS (HR: D-Rd, 0.53; D-VMP, 0.57; VRd, 0.77) and OS (HR: D-Rd, 0.68; VRd, 0.77; D-VMP, 0.78) for NDMM patients. Among them, D-Rd ranked first as the most effective treatment in terms of PFS and OS.…”
Section: Expert Opinionmentioning
confidence: 99%